2021
DOI: 10.1097/mph.0000000000002136
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Scoring Tool to Predict Hydroxyurea Response Among β-Thalassemia Major Patients in Pakistan

Abstract: Despite high prevalence and incidence of β-thalassemia in Pakistan, there is very limited work on the use of hydroxyurea (HU) in thalassemia patients in the country. This is the first insight regarding genetic profiling of BCL11A and HU responses in Pakistani β-thalassemia. It correlates single-nucleotide polymorphisms on BCL11A (rs4671393, rs766432) and HBG2 (XmnI), age at first transfusion, and β-globin mutations with HU response in β-thalassemia major (BTM). Of 272 patients treated with HU, 98 were complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, 20% demonstrated a partial response and 43.75% demonstrated no response to HU. 14 This called for a search for an adjunct or alternative therapy to improve the outcomes in these patients. Thalidomide is an immune modulator that is being studied for its HbF induction potential and has demonstrated significant transfusion reduction in patients with BTM and BTI.…”
Section: Introductionmentioning
confidence: 99%
“…However, 20% demonstrated a partial response and 43.75% demonstrated no response to HU. 14 This called for a search for an adjunct or alternative therapy to improve the outcomes in these patients. Thalidomide is an immune modulator that is being studied for its HbF induction potential and has demonstrated significant transfusion reduction in patients with BTM and BTI.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, specific SNPs in Xmn1 and BCL11A genes were correlated with Hydroxyurea (HU) response in Pakistani β-Thalassemia patients and found that although BCL11A polymorphisms were more prevalent in the Hydroxyurea (HU) responders, their association with HU response was not found to be statistically significant. 12 Other studies investigated Xmn1 polymorphisms in Pakistani thalassemia patients using polymerase chain reaction. [13][14][15][16] The presence of rs4671393 Polymorphisms in mentioned patients (Control, B-thalassemia, S-Bthalassemia), has been compared with their fetal hemoglobin levels by Kruskal-Wallis test.…”
Section: Discussionmentioning
confidence: 99%